Direct comparison of PMT and SiPM PET systems using modified NEMA IEC Body phantom - Ptáček, Jaroslav; Karhan, Pavel; Horňák, Gregor; Quinn, Libuše (Physica medica, 2025)
PURPOSE: This study aimed to compare the image quality of the Siemens Biograph mCT40 (photomultiplier-based system - PMT) and the Siemens Vision600 (silicon photomultiplier-based system - SiPM) using a modified NEMA IEC Body phantom (Data Spectrum). METHODS: SiPM-based Vision600 has a smaller crystal size (3.2 × 3.2 mm vs. 4.0 × 4.0 mm in the PMT-based mCT40), resulting in better spatial resolution. Enhanced time-of-flight (TOF) timing and higher sensitivity leads to nearly four times higher effective sensitivity. The standard NEMA IEC Body phantom was modified with a 3D-printed holder to accommodate also Hollow and Micro Hollow Spheres of 15.4 mm, 12.4 mm, 7.9 mm, 6.2 mm, 5.0 mm, and 4.0 mm. Each of the three acquisition sessions per scanner included 18 time points and spanned 5.6 half-lives to assess system performance at varying activity concentrations in the field of view. RESULTS: Recovery curves for both systems were similar when identical post-reconstruction filters were applied. The SiPM-based Vision600 system detected smaller sources at significantly lower activity concentrations, and the variations in standardized uptake value (SUVmax, SUVA50) measurements were generally smaller compared to those of the PMT-based system. The two smallest sources became undetectable below 63 MBq and 16 MBq on the PMT system, versus 20 MBq and 6.5 MBq on the SiPM system. CONCLUSIONS: SiPM technology demonstrated superior performance compared to PMT in detecting small sources in low-activity scenarios and provided more robust quantification results. It is recommended to use averaged SUV metrics, such as SUVA50 or SUVpeak.
Keywords: Phantoms, Imaging; Positron-Emission Tomography; pozitronová emisní tomografie; počítačové zpracování obrazu; Image Processing, Computer-Assisted; křemík; Silicon; fantomy radiodiagnostické